Analisis Pengaruh Penambahan Lumpur Gambut Terhadap Penurunan Kekeruhan, Zat Organik, Dan Warna Air Gambut Dengan Cara Koagulasi Menggunakan Koagulan Poly Alumunium Chloride (PAC) - Adhani Nindri Afrilia; Dewi Fitria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The presence of Water the peat found in Riau and the water potential used as a source of drinking water. Peat water containing high organic so it needs processing before use. The content of organic substances and the high color in peat water hard to set aside with the process of coagulation – flocculation process, so in this study added peat mud. This study aims to determine the effect of the addition of peat mud in the process of coagulation-flocculation process using coagulant Poly Aluminum Chloride (PAC) 1%. The concentration of the peat Mud used is of 3 g/L, of 5 g/L, 7 g/L, 9 g/L and 11 g/L. Stirring quickly used 150 rpm for 1 minute and stirring slow 70 rpm, 50 rpm, and 30 rpm each for 30 minutes. From the results of the research with the addition of sludge concentration turbidity increased slightly, the concentration of organic substances decreased and the concentration of color decreased when compared with no addition of peat mud.Key words: Coagulation and Flocculation, Color, Organic Substance, Peat Water, Peat Mud, and Turbidity.